ANALISA KEKUATAN TARIK PADUAN ALUMINIUM DENGAN SILIKON PADA DUDUKAN SHOCKBREAKERUKURAN 70 X 30 X 30 mm - Risalah Zakaria (Universitas Hasyim Asy'ari, 2018)
Shockbreaker holder is an additional component in the vehicle that serves as enhancer to fit the posture or as desired from the user.Shockbreaker stands are made from aluminum base material combined with other alloys to improve the mechanical properties of aluminum. So it is necessary to do research using experimental method there is Aluminum-Silicon alloy.The purpose of this researchis to know the tensile strength and strain value on aluminium castings with silicon on shockbreaker stand with variation of silicon 5%, 10%, and 15%. The results of this study showed that tensile strength and strain obtained from 5% silicon alloys were 91.64 MPa and 0.0035%. While the tensile strength and strain obtained from 10% silicon alloys were 109.06 MPa and 0.0038%. While the tensile strenght and strain obtained from 15% silicon alloys are 135.56 MPa and 0.0049%. The best result of aluminium siliconalloy with 15% addition of silicon obtained tensile strength is 135.56 MPa and strain value is 0.0049%